Project management case studies - Kerzner, Harold
"Case studies have traditionally made up a significant portion of project management education and training. The Kerzner Case Studies book was planned to package a broad range of case studies to be used in college or professional training courses as an ancillary to either Kerzner's Project Management book, or other related texts. Case Studies has grown to become a very successful product on its own. For this sixth edition, the author has added 10 new case studies, featuring a variety of industries, and has updated other case studies to meet today's industry standards"--Provided by publisher.